Vertigo Screening And Physiotherapy Intervention - Fithriany; Sri Alna Mutia; Nila Kusma; Amelia Fadlina (JKA, 2024)
Vertigo is a common and often debilitating condition that presents significant challenges in diagnosis and management. Despite advancements in the understanding of the vestibular system and the development of diagnostic tools, there is a lack of long-term data on the natural course of different forms of vertigo and the efficacy of available treatments. This gap in the evidence base makes it difficult to develop standardized diagnostic criteria and improve treatment strategies. To address these issues, an integrated center for research and treatment of vertigo, balance, and ocular motor disorders has been established in Munich, with the goal of improving diagnosis, treatment, and understanding of these disorders. One promising approach to the management of vertigo is through the use of physiotherapy interventions, which can play a significant role in promoting functional reorganization of the vestibular system and improving patient outcomes. However, further research is needed to establish the optimal treatment strategies and their long-term effectiveness.